A biplanar X-ray approach for studying the 3D dynamics of human track formation. Issue 121 (August 2018) - Hatala, Kevin G.; Perry, David A.; Gatesy, Stephen M.
Abstract: Recent discoveries have made hominin tracks an increasingly prevalent component of the human fossil record, and these data have the capacity to inform long-standing debates regarding the biomechanics of hominin locomotion. However, there is currently no consensus on how to decipher biomechanical variables from hominin tracks. These debates can be linked to our generally limited understanding of the complex interactions between anatomy, motion, and substrate that give rise to track morphology. These interactions are difficult to study because direct visualization of the track formation process is impeded by foot and substrate opacity. To address these obstacles, we developed biplanar X-ray and computer animation methods, derived from X-ray Reconstruction of Moving Morphology (XROMM), to analyze the 3D dynamics of three human subjects' feet as they walked across four substrates (three deformable muds and rigid composite panel). By imaging and reconstructing 3D positions of external markers, we quantified the 3D dynamics at the foot-substrate interface. Foot shape, specifically heel and medial longitudinal arch deformation, was significantly affected by substrate rigidity. In deformable muds, we found that depths measured across tracks did not directly reflect the motions of the corresponding regions of the foot, and that track outlines were not perfectly representative of foot size. These results highlight the complex, dynamic nature of track formation, and the experimental methods presented here offer a promising avenue for developing and refining methods for accurately inferring foot anatomy and gait biomechanics from fossil hominin tracks.